2020
DOI: 10.1002/cbic.202000003
|View full text |Cite
|
Sign up to set email alerts
|

Circular Nucleic Acids: Discovery, Functions and Applications

Abstract: acids (CNAs) are nucleic acid molecules with a closed-loop structure. This feature comes with a number of advantages including complete resistance to exonuclease degradation, much better thermodynamic stability, and the capability of being replicated by a DNA polymerase in a rolling circle manner. Circular functional nucleic acids, CNAs containing at least a ribozyme/DNAzyme or a DNA/RNA aptamer, not only inherit the advantages of CNAs but also offer some unique application opportunities, such as the design of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 298 publications
2
34
0
Order By: Relevance
“…The ring structures add to the weight of evidence that the oligomers synthesized by wetdry cycles resemble RNA in their physical properties 23,24 , and similar ring structures has 210 been observed with DNA 25 . Furthermore, the sizes of the rings are well beyond the minimum range required for catalytic or genetic structures to form.…”
supporting
confidence: 71%
“…The ring structures add to the weight of evidence that the oligomers synthesized by wetdry cycles resemble RNA in their physical properties 23,24 , and similar ring structures has 210 been observed with DNA 25 . Furthermore, the sizes of the rings are well beyond the minimum range required for catalytic or genetic structures to form.…”
supporting
confidence: 71%
“…The approach was to develop a closed circular RNA coding for miRNAs. A circular RNA is not readily degraded by exonucleases and the inherent higher stability of dsRNAs compared with ssRNAs may contribute to an increased half-life (34). Increased stability of db34a compared with linear RNA was observed in the present study.…”
Section: Discussionsupporting
confidence: 44%
“…Sanger et al (13) first identified the structural characteristics of circRNA, which comprise a single-stranded, highly stable and closed loop structure lacking a 5'cap or 3'poly-A tail. Numerous circRNA molecules have been identified in eukaryotic cells and tissues and were found to be constructed from selective exonic and intronic repeats that base-pair to one another (14). The involvement of back-splicing and exon-skipping in circRNA formation have been confirmed in vitro and in vivo (15).…”
Section: Biogenesis and Function Of Circrnamentioning
confidence: 98%